The impact of regulation and competition on the migration from old to new communications infrastructure: Recent evidence from EU27 member states - Wolfgang Briglauer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
Fibre-deployment of next-generation communications networks is currently a major challenge for investing firms as well as for national regulators and is also subject to hot debates at EU level. This work examines the role of regulatory policies and competition controlling for relevant supply and demand side factors. Our econometric model employs dynamic panel data methods that take into account potential endogeneity due to omitted heterogeneity, reverse causality and the dynamic investment specification. Our results indicate that relevant forms of previous broadband access regulations have had a negative impact on investment in new infrastructure. Furthermore, infrastructure-based competition from mobile operators and the replacement effect stemming from the incumbents' existing infrastructure exert a negative impact on ex ante investment incentives. As regards the dynamics of the adjustment process, we find that there are both short-term and long-term effects towards the desired infrastructure level.
urn:nbn:de:bsz:180-madoc-373070
Keywords: H5; L38; L43; L52; 330; next-generation communications networks; sector-specific regulation; infrastructure competition; investment conditions; adjustment process; EU27 panel data